2016
DOI: 10.3389/fpsyg.2016.00912
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Mindfulness Training in the Treatment of Fatigue After Stroke, Traumatic Brain Injury and Multiple Sclerosis: A Systematic Literature Review and Meta-analysis

Abstract: Background: Fatigue is a common symptom following neurological illnesses and injuries, and is rated as one of the most debilitating sequela in conditions such as stroke, traumatic brain injury (TBI), and multiple sclerosis (MS). Yet effective treatments are lacking, suggesting a pressing need for a better understanding of its etiology and mechanisms that may alleviate the symptoms. Recently mindfulness-based interventions have demonstrated promising results for fatigue symptom relief.Objective: Investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 93 publications
1
39
0
Order By: Relevance
“…Lack of significant difference in social functioning subscale between experimental and control group can be affected by different factors such as family relationships, culture, attitude and economic condition in individuals. Like our study, Henderson et al, 32 Carletto et al, 33 and Ulrichsen et al, 34 showed that the treatment of MBSR highly affected on the quality of life, well-being, and hope in Traumatic Brain Injury and MS samples and significantly in reducing subscales of depression, anxiety, and hostility.…”
Section: Discussionsupporting
confidence: 76%
“…Lack of significant difference in social functioning subscale between experimental and control group can be affected by different factors such as family relationships, culture, attitude and economic condition in individuals. Like our study, Henderson et al, 32 Carletto et al, 33 and Ulrichsen et al, 34 showed that the treatment of MBSR highly affected on the quality of life, well-being, and hope in Traumatic Brain Injury and MS samples and significantly in reducing subscales of depression, anxiety, and hostility.…”
Section: Discussionsupporting
confidence: 76%
“…We successfully recruited men, non-whites, and patients with different types of cancer; 32% of patients were male, 20% were non-white, and over 60% of patients had cancers other than breast. Previous mindfulness studies for cancer patients overwhelmingly consisted of white, early stage breast cancer patients who had completed all of their initial treatment (Piet et al, 2012; Ulrichsen et al, 2016). Few mindfulness studies have focused on patients who are actively undergoing chemotherapy or patients with more advanced stages (Chambers et al, 2017; Lengacher et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with a systematic review that concluded that mindfulness was effective in women with breast cancer at improving fatigue, quality of life and sleep. [25] Other systematic reviews have suggested that mindfulness may reduce fatigue in traumatic brain injury, [26] stroke [27] and multiple sclerosis. [27] We also found that relaxation techniques were effective at improving fatigue symptoms, consistent with a review that evaluated exercise and nonpharmaceutical interventions for CRF and used indirect comparisons to conclude that relaxation was the highest ranked intervention for fatigue reduction.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Other systematic reviews have suggested that mindfulness may reduce fatigue in traumatic brain injury, [26] stroke [27] and multiple sclerosis. [27] We also found that relaxation techniques were effective at improving fatigue symptoms, consistent with a review that evaluated exercise and nonpharmaceutical interventions for CRF and used indirect comparisons to conclude that relaxation was the highest ranked intervention for fatigue reduction. [28] Other systematic reviews have also suggested that relaxation techniques may reduce fatigue in osteoarthritis, [29] heart failure [30] and kidney disease.…”
Section: Discussionmentioning
confidence: 99%